Innovative Liposomal Delivery System from Hermetia illucens Oil Entrapped Curcuma aromatica Extract: Effect on Matrix Metalloproteinase-1 (MMP-1) - Kornchanok Srisombat (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this study is to fabricate an innovative delivery system from Black soldier fly (Hermetia illucens) larvae oil (BSFL oil). Major components in this oil are natural origin-fatty acids and phospholipids, which were applied to the formation of lipid-based nanoparticles entrapped the plant extract model Curcuma aromatica Salisb (CA) rhizomes. CA has been widely used in Asian traditional medicines and cosmetics proposed for anti-melanogenic, anti-inflammatory and anti-tumor. However, poor-stability, and poor-solubility of curcuminoids, major compounds in CA extract (CAE) are the limitations for incorporation of CAE in topical formulations. Hence, the liposome composted of BSFL oil, cholesterol and Span 60 developed by the conventional film method in this research. Characteristics (i.e. size, polydispersity index, zeta potential, entrapment efficacy, release profile) of the optimized liposome entrapped with CAE were investigated. The transdermal ability criteria of the developed liposomes were met, i.e. spherical shape with a small particle size approximately 180 nm, narrow size distribution (PDI < 0.3) with the zeta potential of -34 mV. Significant entrapment of the curcuminoids in liposome was greater than 90% with sustained-release ability. The developed liposomes entrapped with CAE were evaluated on skin care potential through the in vitro matrix metalloproteinase-1 (MMP-1 or collagenase), elastase and hyaluronidase inhibition assay. The present study concludes that BSFL oil could efficiently entrap the CAE, allowing the application of the colloidal curcuminoids in aqueous-based formulation. This BSFL oil from Black solider fly was proven as a potential lipid source for liposome or lipid-based nanocarrier delivery system in this study.